Revisiting Multiple Intelligence Theory to Boost Writing Performance - Cemile Doğan (Literacy Trek, 2019)
This experimental study aimed to investigate the effect of Multiple Intelligence Theory on EFL learners’ writing performance. The issue of stimulating learners to become better writers was addressed through using a selection of activities prepared to trigger the multiple intelligences defined by the founder of Multiple Intelligence theory, Howard Gardner. In the study, both experimental and control groups analyzed the same materials. The course of treatment for the experimental group was outlined through inclusion of multiple intelligences activities during ‘while-stage’ of writing. In the control group, on the other hand, there was not any intervention in the planned flow. The results of the study yielded that the learners whose multiple intelligences were activated during implementation displayed better performance in writing. The findings are discussed in line with the current status and several implications are provided for utilizing the multiple intelligences in ELT.